COVID-19 vaccination and relapse activity: A nationwide cohort study of patients with multiple sclerosis in Denmark - Stastna, Dominika; Elberling, Frederik; Pontieri, Luigi; Framke, Elisabeth; Horakova, Dana; Drahota, Jiri; Nytrova, Petra; Magyari, Melinda (European journal of neurology, 2024)
BACKGROUND AND PURPOSE: We evaluated whether there was a difference in the occurrence of relapses pre- and post-COVID-19 vaccination in a nationwide cohort of Danish patients with relapsing multiple sclerosis. METHODS: We conducted a population-based, nationwide cohort study with a cutoff date of 1 October 2022. We used McNemar tests to assess changes in the proportion of patients with recorded relapses within 90 days and 180 days before and after first vaccine dose, and a negative binomial regression model to compare the 90 and 180 days postvaccination annualized relapse rate (ARR) to the 360 days prevaccination ARR. Multivariate Cox regression was used to estimate relapse risk factors. RESULTS: We identified 8169 vaccinated (87.3% Comirnaty) patients without a recorded history of a positive COVID-19 test. We did not find statistically significant changes in the proportion of patients with relapses in the 90 days (1.3% vs. 1.4% of patients, p = 0.627) and 180 days (2.7% vs. 2.6% of patients, p = 0.918) pre- and postvaccination. Also, a comparison of the ARR 360 days before (0.064, 95% confidence interval [CI] = 0.058-0.070) with the ARR 90 (0.057, 95% CI = 0.047-0.069, p = 0.285) and 180 (0.055, 95% CI = 0.048-0.063, p = 0.060) days after vaccination did not show statistically significant differences. Lower age, higher Expanded Disability Status Scale score, and relapse within 360 days before vaccination were associated with a higher risk of relapse. CONCLUSIONS: We did not find evidence of increased relapse activity following the administration of the first dose of the COVID-19 vaccine.
Keywords: multiple sclerosis; safety; Recurrence; Dánsko; vaccine; vakcinace; relabující-remitující roztroušená skleróza; lidé; Multiple Sclerosis; recidiva; roztroušená skleróza; vakcíny proti COVID-19; COVID-19; kohortové studie; relapse; Cohort Studies; Vaccination; Multiple Sclerosis, Relapsing-Remitting; chronická nemoc; COVID-19 Vaccines; Chronic Disease; Denmark; Humans